(3EMcGe GdaUhd aj CMcGe GdCUhds - (3SdjeGf Hf Nda Hf SYO GdJLjHj GdbQWHj, CHh GdhdjO GdHGLj,J (B474 (3g` s ((3eMeO CMeO eMeO GdJejei s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CQTOfG Edi efGgL SHdg CeG HYO aEfc SCdJfi Cf CLeY dc cJGHkG ai Led CbhGd GdeGdcjjf s
(3BNQgG (B:s
(3jfJgi HaUd ajeG EPG cGfJ EMOi GdYdJjf ehLHg ddYJb hGdCNQi ZjQ ehLHI dg hLhGH BNQ hgh Cf GdJZdjH hGdSQGjI EfeG JMUd HYO hbhYg ajXd eG bGdhg s
(3YdjgG JMHjS Ydi LGeY GdCfOdS HaGS SfI (B931s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B261s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs